A hamis beismerő vallomást eredményező befolyásolás a büntetőeljárásban - Elek, Balázs (Debreceni Jogi Műhely, 2007)
Often justice would be less miscarry, if all who were about to weigh evidence had more conscious of the treachery of human memory. The memory ideas of a person are objective reproductions of earlier experience or are mixed up with associations and suggestions. The possibility exists that police might obtain a confession from an innocent person in a crime he had never committed. It is even possible that false confession might lead to a false conviction. The power of suggestion devastates memory, and this remains entirely within the limits of the normal healthy individuality. If interviewing techniques were to be assessed in terms of the police claim that they are geared to an objective reach for the truth, then they would emerge as thoroughly deficient. The progress of psychological science can not be further ignored.